2013
DOI: 10.1155/2013/761971
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Modification, and Emerging Applications of TiO2Nanotube Arrays by Electrochemical Synthesis: A Review

Abstract: Titania nanotube arrays (TNAs) as a hot nanomaterial have a unique highly ordered array structure and good mechanical and chemical stability, as well as excellent anticorrosion, biocompatible, and photocatalytic performance. It has been fabricated by a facile electrochemical anodization in electrolytes containing small amounts of fluoric ions. In combination with our research work, we review the recent progress of the new research achievements of TNAs on the preparation processes, forming mechanism, and modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 153 publications
(184 reference statements)
3
33
0
3
Order By: Relevance
“…Surprisingly, though, both techniques resulted in anodic films even thinner than those grown using the previously discussed medium film protocols (those using low fluoride concentrations). The results from these high fluoride protocols reinforced the assertions from other studies [87], [93] that higher fluoride concentrations alone are not sufficient to grow thicker films. Higher potentials are necessary to promote the fieldaided ionic transport and targeted anodic dissolution at the base of the nanotubes rather than general dissolution at the outer portions of the anodic films.…”
Section: Protocol: 50 Volt 4 Hour High Fluoride New Electrolytesupporting
confidence: 84%
See 3 more Smart Citations
“…Surprisingly, though, both techniques resulted in anodic films even thinner than those grown using the previously discussed medium film protocols (those using low fluoride concentrations). The results from these high fluoride protocols reinforced the assertions from other studies [87], [93] that higher fluoride concentrations alone are not sufficient to grow thicker films. Higher potentials are necessary to promote the fieldaided ionic transport and targeted anodic dissolution at the base of the nanotubes rather than general dissolution at the outer portions of the anodic films.…”
Section: Protocol: 50 Volt 4 Hour High Fluoride New Electrolytesupporting
confidence: 84%
“…Anodizing methods for creating nanofeatured films on titanium substrates have been extensively studied under a variety of similar conditions [61], [87][88][89][90][91][92][93][94]. The varying methods differ in substrate thickness, surface preparation, electrolyte composition, electrolyte concentration, anodizing potential, and anodizing duration.…”
Section: B Background On the Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…One can functionalize titania and TNT or enhance its initial functional (sensor, catalytic, and other) properties via its modification with metals and, in par ticular, noble metal nanoparticles (Ag, Au, Pt, Pd, their alloys) [20][21][22]. For example, the studies of cat alytic activity of nanotubular titania coated by gold nanoparticles with respect to oxygen reduction reac tion showed that it is three times as much as that for flat gold electrode [23].…”
Section: Introductionmentioning
confidence: 99%